The Impact of Age and Disease Entity on Small Airway Dysfunction in Obstructive Airway Diseases - Li Y; Su KC; Hsiao YH; Chou KT; Li YJ; Jeng TH; Ko HK; Perng DW (International Journal of COPD)
Yang Li,1 Kang-Cheng Su,1,2 Yi-Han Hsiao,1,2 Kun-Ta Chou,1,2 Yen-Jung Li,1 Tien-Hsin Jeng,1,3 Hsin-Kuo Ko,1,2 Diahn-Warng Perng1,2 1Department of Chest Medicine, Taipei Veterans General Hospital, Taipei, 11217, Taiwan, Republic of China; 2School of Medicine, College of Medicine, National Yang Ming Chiao Tung University, Taipei, 11221, Taiwan, Republic of China; 3Division of Pulmonary Medicine, Department of Internal Medicine, Ditmanson Medical Foundation Chia-Yi Christian Hospital, Chia-Yi, 60002, Taiwan, Republic of ChinaCorrespondence: Diahn-Warng Perng, Department of Chest Medicine, Taipei Veterans General Hospital, No. 201, Sec. 2, Shih-Pai Road, Taipei, 11217, Taiwan, Republic of China, Tel +886 2 28712121, ext., 27034, Fax +886 2 28752380, Email dwperng@vghtpe.gov.twPurpose: Small airway dysfunction (SAD) is prevalent in asthma and chronic obstructive pulmonary disease (COPD). Aging is acknowledged to be associated with the loss of small airway structures. However, the impact of aging and pathophysiological changes on SAD in asthma and COPD remains unclear. We aimed to investigate the impact of aging and disease entity on pathophysiological change-related SAD in asthma and COPD assessed by spirometry and impulse oscillometry (IOS).Patients and Methods: We retrospectively reviewed adult patients diagnosed with asthma or COPD between May 2017 and August 2021 in Taipei Veterans General Hospital. Treatment-naïve COPD patients aged ≥ 60 years were enrolled, along with age- and gender-matched elderly asthmatics (EA), and younger asthmatics aged < 60 years (YA) for comparison. All participants underwent spirometry and IOS with a bronchodilator test. Blood eosinophil counts (BECs) and immunoglobulin E(IgE) levels were documented if blood tests were conducted at the time of diagnosis.Results: The mean age of YA, EA, and COPD were 44, 73, and 73 years, respectively. The FEV1, FEV1/FVC and FEF25-75% were higher in the YA followed by EA and COPD groups. The spirometric values were significantly correlated with IOS parameters in both asthmatic and COPD groups. No significant differences were observed in baseline IOS parameters among the three groups for participants with FEV1 ≥ 80% predicted. However, in patients with FEV1< 80% predicted, COPD patients exhibited significantly worse spirometric values and most IOS parameters (except R5-R20) compared to asthmatics. Additionally, asthmatics with AX reduction ≥ 35% exhibited significantly higher levels of blood eosinophil counts and IgE.Conclusion: Aging process contributes to more impact on small airway reactance in asthma, while disease entity in COPD exhibits worse spirometric and IOS parameters compared to the age- and gender-matched EA.Keywords: aging, elderly asthma, chronic obstructive pulmonary disease, COPD, impulse oscillometry, IOS, small airway dysfunction, SAD